Le Musée des Beaux-Arts du Canada : une histoire du vivre ensemble - Véronique Stahn (Conserveries Mémorielles)
The history of the National Gallery of Canada belongs to the history of national museums in society since the 19th century. Its creation is linked to canadian national identity in the era of the birth of nationalisms. This paper tries to put the birth of the museum in the context of history, memory and patrimonial transmission, which are central problematics in regard of the history of museums in the 19th and 20th centuries.